2016
DOI: 10.1002/2016jc011887
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal predictability of sea surface temperature anomalies over the Kuroshio‐Oyashio Extension: Low in summer and high in winter

Abstract: The seasonal predictability of sea surface temperature anomalies (SSTA) in the Kuroshio‐Oyashio Extension (KOE) is explored by performing perfect model predictability experiments from the viewpoint of initial error growth in a global coupled model. It is found that prediction errors of KOE‐SSTA always increase in the boreal summer and decrease in the boreal winter. This leads to smaller (larger) prediction errors and higher (lower) prediction skills in boreal winter (summer). This seasonal characteristic of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Duan and Wu (2014) identified a “summer prediction barrier” in Pacific decadal oscillation‐related SST anomalies, emphasizing the challenges in mid‐latitude predictions from the perspective of initial error growth in perfect model predictability experiments. The seasonal predictability of SST anomalies in the KOE also exhibited seasonal dependence (Wu & Duan, 2018; Wu et al., 2016). The predictability of North Pacific SST requires further study.…”
Section: Introductionmentioning
confidence: 99%
“…Duan and Wu (2014) identified a “summer prediction barrier” in Pacific decadal oscillation‐related SST anomalies, emphasizing the challenges in mid‐latitude predictions from the perspective of initial error growth in perfect model predictability experiments. The seasonal predictability of SST anomalies in the KOE also exhibited seasonal dependence (Wu & Duan, 2018; Wu et al., 2016). The predictability of North Pacific SST requires further study.…”
Section: Introductionmentioning
confidence: 99%
“…In the western central North Pacific, initial error growth also exhibits a distinctive seasonal dependence. The prediction skill is lowest in summer, giving rise to the summer predictability barrier (Zhao et al, 2012;Duan and Wu, 2014;Wu et al, 2016). Previous researches suggested that a shallow mixed-layer depth in the North Pacific accompanied by strong oceanic stratification in summer could result in a relatively weak correlation between SSTAs in the summer and temperature in the following winter (Alexander, 1999;Jacox et al, 2019), which could lead to poor prediction of SSTAs.…”
Section: Introductionmentioning
confidence: 99%